Tecnologías blandas en la gestión administrativa de las empresas constructoras mipymes (2015)
One of the most serious problems within the PYMES Construction Companies (hereinafter PCC) is the low technological capability both in administrative and production to compete successfully in a highly competitive and globalized environment, as can be corroborated in the diagnosis of CAMACOL, “Pymes enterprises on the construction industry”, (Cámara Colombiana de la Construcción [CAMACOL], 2010) The low level of investment and technological development at the organizational level and production has led the PCC to a doubly lagging unequal relationship, of delay with respect to the technological advances of the production centers and the predominance of the market by large firms in the domestic environment.